KRITIK TERHADAP ILMU SEBAGAI PANDANGAN DUNIA MODERN DALAM PERSPEKTIF KAWRUH BIMOSUCI - Slamet Sutrisno (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2009)
AbstractThe modern culture has a big influence in all over the world. The big influence, especially on developing of modern culture or modernity to modernism, makes hegemony on the cultures of non-Western. It states that the modern worldview has operated its hegemony toward non-western ones. All segments of modern worldview base on thought and the modern culture of thought is science.Kawruh Bimosuci as a Javanese worldview is a Javanese gnosis and very potential to rise a collective awareness in order toreconstruct on a worldwide scale culture accompanying its characters that go to compatibility with the ideational cultureaccording to Pittirim Sorokin. Kawruh Bimosuci is able to develop critically a new vision of culture. The capability takes place in the ideas domain and, moreover, a national self-identity in the current modern hegemony that its basis is the hegemony of modern worldview toward the Eastern tradition and system of knowledge.Keyword: Kawruh Bimosuci, worldview, science, hegemony,dialogue-dialectic.